The Formation of the Swiss Hospital System (1840–1960) An Analysis of Surgeon-Modernisers in the Canton of Vaud - Donzé, Pierre-Yves (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
XIV, 221 p. 19 illus., 1 illus. in color.